2020
DOI: 10.1186/s13014-020-1468-9
|View full text |Cite
|
Sign up to set email alerts
|

Automated Hypofractionated IMRT treatment planning for early-stage breast Cancer

Abstract: Background: Hypofractionated whole-breast irradiation is a standard adjuvant therapy for early-stage breast cancer. This study evaluates the plan quality and efficacy of an in-house-developed automated radiotherapy treatment planning algorithm for hypofractionated whole-breast radiotherapy. Methods: A cohort of 99 node-negative left-sided breast cancer patients completed hypofractionated whole-breast irradiation with six-field IMRT for 42.56 Gy in 16 daily fractions from year 2016 to 2018 at a tertiary center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
3
26
0
2
Order By: Relevance
“…Each iteration proceeds in a trial‐and‐error fashion, with the planner editing the fluence, calculating 3D dose, and evaluating the dose until “optimal” dosimetry is achieved. There are several published studies on automated treatment planning algorithms being implemented for various anatomical sites, including breast 8–16 . Many institutions use in‐house developed software for plan automation, and while that is a feasible solution for those that already have it or have the resources to develop, maintain,and validate in‐house solutions, such an approach may not be accessible for many nonacademic clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each iteration proceeds in a trial‐and‐error fashion, with the planner editing the fluence, calculating 3D dose, and evaluating the dose until “optimal” dosimetry is achieved. There are several published studies on automated treatment planning algorithms being implemented for various anatomical sites, including breast 8–16 . Many institutions use in‐house developed software for plan automation, and while that is a feasible solution for those that already have it or have the resources to develop, maintain,and validate in‐house solutions, such an approach may not be accessible for many nonacademic clinics.…”
Section: Discussionmentioning
confidence: 99%
“…There are several published studies on automated treatment planning algorithms being implemented for various anatomical sites, including breast. [8][9][10][11][12][13][14][15][16] Many institutions use in-house developed software for plan automation, and while that is a feasible solution for those that already have it or have the resources to develop, maintain,and validate in-house solutions, such an approach may not be accessible for many nonacademic clinics. Commercially available software such as EZF, therefore can provide an ideal solution for those that have limited time and resources.…”
Section: Discussionmentioning
confidence: 99%
“…There have been excellent studies to develop automated tools for breast treatment planning processes with the goals of improving planning efficiency and standardizing plan quality. 18 , 19 , 20 , 21 , 22 , 23 Those tools were developed to automate 3D CRT, 18 field-in-field, 19 , 23 or intensity modulated radiation therapy techniques. 21 , 22 Our auto-planning tool was developed based on the irregular surface compensator technique because our institution has been using it for over 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rings around the target, with different thicknesses and locations, were used to restrict the dose distribution for the target and intermediate-high dose for the ipsilateral lung (22). Xu et al used a blocking structure to block low doses in the lungs (23), while Lin et al demonstrated the use of conformed rings as dose constraint structures for whole-breast radiotherapy planning (24). The two different rings can separately restrict the unwanted intermediate-high dose for the ipsilateral lungs and heart, and the low dose for the contralateral lung.…”
Section: Introductionmentioning
confidence: 99%
“…used a blocking structure to block low doses in the lungs ( 23 ), while Lin et al. demonstrated the use of conformed rings as dose constraint structures for whole-breast radiotherapy planning ( 24 ). The two different rings can separately restrict the unwanted intermediate-high dose for the ipsilateral lungs and heart, and the low dose for the contralateral lung.…”
Section: Introductionmentioning
confidence: 99%